ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Nadya Ayu Saputri; Rochmi Widayanti; Ratna Damayanti (ITB AAS INDONESIA Surakarta, 2019)
The purpose of the study was to analyze the effect of the application of good corporate governance, which was governed by the board of commissioners, board of directors, audit committee and institutional ownership of financial performance which was interpreted by the return on asset ratio in banking companies on the Indonesia Stock Exchange for the period 2014-2017. The total population is 43 companies, using purpose sampling techniques obtained by a sample of 25 companies. While the analysis technique used is multiple linear regression. The results show that only the audit committee that has no significant effect, the board of commissioners has a significant negative effect on the board of directors and institutional ownership has a significant positive effect on financial performance. Other results show that simultaneous application of good corporate governance has a significant influence on financial performance. Keyword: good corporate governance, financial performance.